The Implementation Of Instagram In Mastering Arabic Vocabulary Among The Millennial Generation In The MTSN 2 Jember - Maulana, feri; Priyono , Dwi Juli; Maulana, Bayu Wahyu; Shoubaki, Hamza (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to determine the effectiveness of the use of Instagram media in  learning the Arabic language, especially vocabulary, in the millennial generation.  The qualitative method uses a descriptive approach according to the issues at hand,  which is the effectiveness of Instagram in mastering Arabic vocabulary among  millennials. The results of this study indicate that Instagram is one of the social  media that supports learners (the millennial generation) to learn, understand and  memorise Arabic vocabulary without being restricted by time and place. Based on  the results of an online survey given to the students who received positive  responses, six agreed to use Instagram to learn Arabic vocabulary. Students  responded positively because it was flexible, interesting, timeless, and creative.  Negative response because it requires an internet connection, and learning cannot  be implemented directly. Through this research, it is hoped that millennials can use  Instagram media wisely, such as technology, to gain knowledge and expand their  horizons.